Drivers and Outcomes of Green Tourist Attitudes and Behavior: Sociodemographic Moderating Effects - Leonidou, Leonidas C.; Coudounaris, Dafnis N.; Kvasova, Olga; Christodoulides, Paul (My University, 2015)
This article reports the findings of a study, conducted among 234 foreign tourists who visited Cyprus, that aimed to identify the drivers and outcomes of eco-friendly attitudes and behavior. Using structural equation modeling, the authors confirmed that deontological status, law obedience, and political action of tourists positively influence the adoption of an environmentally friendly attitude. In turn, these effects are conducive to eco-friendly behavior, which ultimately enhances tourist satisfaction. Certain sociodemographic characteristics of tourists-namely, gender, age, education, and income-had a moderating effect on the link between deontological status, law obedience, and political action on the one hand and eco-friendly attitudes on the other hand. Tourist nationality also had a control effect on tourist eco-friendly attitudes.
Keywords: Social desirability bias; Environmental attitudes; Planned behavior; Value orientations; Consumer-behavior; Service firms; Intentions; Ecotourism